D6 Dna damage in lymphocytes as a predictor of illness evolution in pre-manifest and overt huntington's disease. (13th September 2016) - Ferraldeschi, Michela; Romano, Silvia; Delmondo, A; Monaco, A; Spadaro, Maria; Frontali, Marina; Ristori, G; Porcellini, A
Abstract : Background: Huntington's disease (HD) is an autosomal dominant neurodegenerative disease caused by a CAG repeat expansion in the HTT gene that encodes huntingtin (HTT). Mutant HTT leads to abnormalities in cellular function and transcriptional dysregulation that have long been recognised as central to the pathogenesis of HD. Our previous work showed that expression for 3 h of a polyQ-expanded protein (GPF-polyQ, Ataxin-2 and Huntingtin) stimulated cellular reactive oxygen species (ROS) levels and significantly reduced the mitochondrial electrochemical gradient. This result suggest that mutant HTT-induced oxidative stress may lead to persistent activation of DNA damage response (DMR) that may represent an early, main cause of neuronal dysfunction. Methods: To quantify DMR, we used cytofluorimetric analysis to detect phosphorylated H2AX (PH2AH). Blood samples were obtained by venous punctures in EDTA-tubes. Freshly isolated peripheral blood mononuclear cells (PBMC) by differential centrifugation through Ficoll were fixed 10 minutes in 4% paraformaldehyde, made permeable with ice-cold 70% ethanol for 30 min, incubated with anti-Fc to block non-specific binding of Fc receptor expressing cells and incubated with anti-PH2AX. We enrolled pre-manifest HD, stratified according to the risk of motor onset into low, medium and high groups, as previously described; symptomatic HD patients, whose disease severity was quantified according to UHDRS, and healthy subjects as controls. Exclusion criteria were: drugs HDAC inhibitors, or NADP inhibitors and other factors known to interfere with the oxidative status of the subject; concomitant serious illnesses; pregnancy and breast-feeding. Results: We included 14 (female/male ratio 8/6; age F 30.0 ± 6.7; M 41.8 ± 11.68) pre-manifest HD (pre-HD; Mean Repeat: 42.8 ± 2.7); 29 (female/male ratio 11/18; age F 46.7 ± 9.4; M 55.0 ± 10.1) symptomatic HD patients (Mean Repeat: 42.66 ± 1.9) and 18 healthy subjects as controls (C) (female/male ratio 13/5; age F 49.5 ± 9.6; M 45.4 ± 14.3). We found that patients and pre-HD showed a high PH2AH index as compared to the controls (C mean: 2.9 ± 2.02; HD mean: 10.56 ± 6.9; pre-D: 10.6 ± 7.0); the odds ratio was <0.005 (C vs HD: Wilcoxon/Kruskal-Wallis z = −4.32, p < 0.0001; Logistic Fit ChiSquare 23.98, p < 0.0001; ROC Area 0.87, Odds Ratio 0.0000013, p = 0.0035; C vs pre-HD: Wilcoxon/Kruskal-Wallis z = 3.703, p = 0.0002; Logistic Fit ChiSquare 18.53, p < 0.0001; ROC Area 0.89, Odds Ratio 0.0000016, p = 0.0138). Conclusions: These data, albeit preliminary, suggest an association between a high PH2AX index and HD, being promising as biomarker to characterise HD patients and to monitor disease progression.